Study the Appropriate Value of the Roller Clearance in a 4-Roll Raw Rubber Sheet Rolling Machine - Phopha, Surasit; Sasen, Chailai; Saenpong, Anuwat (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
This research article aimed to study the clearance of the second finishing roller set of the 4-roll raw rubber sheet rolling machine affecting the period of rolling para rubber sheets and 4-roll raw rubber sheet rolling machine efficiency as well as electrical energy consumption to rolling para rubber sheets. The experiments were carried out with the following roller clearance settings for each press roller set: the first smooth roller set will be set to a clearance of 4.5 mm, the second smooth roller set to 3.0 mm, the first finishing roller set to 2.0 mm, and the second finishing roller set will be to three levels: 1.0, 0.5, and 0.1 mm. respectively. The result found that the 4-roll raw rubber sheet rolling machine can significantly reduce the overall raw rubber sheet rolling time, decreasing rolling time by 82.40 %. The comparisons of the production rate per hour represented the 4-roll raw rubber sheet rolling machine performs a higher rubber rolling rate than the traditional rolling machine, with an average rolling rate of 361.08 sheets per hour. Furthermore, electrical energy consumption was reduced by 58.126 %. Adjusting the clearance of the second finishing roller set to 0.1 mm provides the average thickness of rubber sheets after rolling as 2.14 mm. which is the standard size, and obtains the highest rolling efficiency of 88.24 %.